Tarif Ijin Perubahan Guna Lahan Perkotaan Sebagai Bentuk Kontrol Pelaksanaan Penataan Ruang Kota - Winarso, Haryo (Journal of Regional and City Planning, 1995)
Land-use changes have been a common phenomena in Indonesian cities. Some of the changes do improve the physical as well as socio economic conditions of the areas, but, in the absence of sound legal procedure for the changes, mostly harms the environment and the people, creates traffic jam and evicts the low income people. Therefore a new legal procedure for land-use changes should be developed. This article will discuss the “development charges’ approach as a legal tool to make land-use change benefits the people, the government and the private sector.